Oracle of Doom or Oracle of Salvation? A New Interpretation of Animal Metaphors in Isa 31:4-5 in the Light of Rhetorical Analysis - Sobierajski, Bartłomiej Paweł (Verbum Vitae, 2021)
This article seeks to clarify the meaning of animal metaphors contained in Isa 31:4-5. Difficulties in interpreting these metaphors are associated with the Hebrew syntax as well as the proper reading of the symbolism of the characters and animals found within these verses. These issues also raise the question of the message of the whole prophecy: is it an oracle of doom or of salvation? The article provides an overview of previous attempts to explicate the metaphors and proposes a new interpretation of them. It turns out that Isaiah consciously and intentionally uses some ambiguous images and formulas in order to make a specific impression on the addresser. Such literary devices are characteristic of his statements from the last period of his activity (705–701 BC). The new interpretation of animal metaphors presented in this study also results from the structure of the oracle, which has emerged through the use of Hebrew rhetoric methods